Student Experience and Quality of Tertiary Education for Students with Disabilities in Lesotho (Journal of Student Affairs in Africa, 2021)
Access to tertiary education in the least developed countries, such as Lesotho, continues to be a rare experience for persons with disabilities who, despite being admitted to studies, struggle with meaningful participation. This article explores student experience of persons with disabilities studying at the National University of Lesotho. A combination of convenience and snowballing sampling techniques were used to recruit 15 staff members and 11 students enrolled in various programmes. A combination of individual semi-structured interviews and a focus group discussion were used to generate data. Findings reveal that various dimensions of student experiences are negatively affected. Students with disabilities encounter mobility challenges due to an inaccessible built environment; lecture timetables are not adapted to suit the needs of students with mobility challenges, blind students are not informed of potholes that are left uncovered and the students’ request for their hostel to be adapted is not addressed. Additionally, students are not readily supported by their lecturers while some are subjected to bullying which goes unpunished and the victims receive no counselling for the resultant trauma. These factors affect the students’ welfare and have an effect on their academic participation. The students are simply expected to conform to university practices. The summary of student experience, if used for assessment of quality education, demonstrates inequitable access to education for persons with disabilities. The study concludes that the institution provides poor-quality education as it fails to address the support needs of students with disabilities. The study recommends development of policies and practices that promote equity, and that student experience can be used to inform how the institution may improve access and the quality of its programmes. Equally, this study challenges students with disabilities to assert their right to an inclusive and equitable quality education
Keywords: ableism; equitable access; quality education; student experience; students with disabilities; tertiary education